Infrastructure: the social value of shared resources - Frischmann, Brett M. (New York : Oxford University Press, 2012)
Infrastructure resources are the subject of many contentious public policy debates, including what to do about crumbling roads and bridges, whether and how to protect our natural environment, energy policy, even patent law reform, universal health care, network neutrality regulation and the future of the Internet. Infrastructure resources are the subject of many contentious public policy debates, including what to do about crumbling roads and bridges, whether and how to protect our natural environment, energy policy, even patent law reform, universal health care, network neutrality regulation and the future of the Internet.